2021
DOI: 10.1002/admi.202100049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Treatment on Metal Oxide p–n Thin Film Diodes Fabricated at Room Temperature

Abstract: There is a need for a good quality thin film diode using a metal oxide p–n heterojunction as it is an essential component for the realization of flexible large‐area electronics. However, metal oxide‐based diodes normally show poor rectification characteristics whose origin is still poorly understood; this is holding back their use in various applications. A systematic study of the origins of the poor performance is performed based on bias‐stress measurements using a cuprous oxide (Cu2O)/amorphous zinc‐tin oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Reproduced under terms of the CC‐BY license. [ 17 ] 2021, Y. J. Khong, K. M. Niang, S. Han, N. J. Coburn, G. Wyatt‐Moon, A. J. Flewitt, published by Wiley.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced under terms of the CC‐BY license. [ 17 ] 2021, Y. J. Khong, K. M. Niang, S. Han, N. J. Coburn, G. Wyatt‐Moon, A. J. Flewitt, published by Wiley.…”
Section: Resultsmentioning
confidence: 99%
“…This observed outcomes may be explained by the shift in equilibrium in the conversion process between ionised oxygen vacancies and electron‐filled states. [ 17 ] The majority of charge carrier contributors in the a‐ZTO layer of the untreated diode are states in the metal oxide constantly shifting between oxygen vacancy states and electron‐filled states depending on Fermi level position favouring the generation of either one. When the alternating current signal from C–V measurement increases, these states are no longer able to follow, and the apparent doping density increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially the green and sufficient solar energy would be the most ideal candidate, [5][6][7][8] such as photocatalytic hydrogen evolution, photocatalytic CO 2 reduction to CH 4 or CO, or solar water heater, and so on. Herein, the photovoltaic device with directly photoelectric conversion would be an efficient method, [9][10][11] such as Emetere et al have reported NaZnBr 3 -based novel perovskite solar cells, [12] etc. However, the traditional photovoltaic devices mainly aim at the ultimate photovoltaic conversion efficiency, that, the adequately solar absorption would lead a significant decreasing in lighting, which would restrict their widely applications, especially in windows or building walls.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the green and sufficient solar energy would be the most ideal candidate, [ 5–8 ] such as photocatalytic hydrogen evolution, photocatalytic CO 2 reduction to CH 4 or CO, or solar water heater, and so on. Herein, the photovoltaic device with directly photoelectric conversion would be an efficient method, [ 9–11 ] such as Emetere et al. have reported NaZnBr 3 ‐based novel perovskite solar cells, [ 12 ] etc.…”
Section: Introductionmentioning
confidence: 99%